The impact of digital marketing on the profitability of selected samples of food-related micro businesses in Makati and Quezon City during the COVID-19 pandemic - Castro, Manuel Antonio M. (Animo Repository, 2022)
With ever-changing technological advancements, most firms use a variety of digital marketing tactics to target clients across a wide range of marketing endeavors. Understanding which strategies to use is critical for food-related micro-businesses. As such, the study looks into the effects of digital marketing on profitability, with a particular focus on chosen samples of food-related micro-businesses in Makati and Quezon City during the COVID-19 pandemic. The researchers devised a questionnaire to assess the impact of internet marketing on the profitability of food-related micro-businesses. A total of three hundred forty-five microbusiness owners/managers took part in the study. According to our findings, digital marketing and e-commerce have substantial relationships with profitability. However, no significant relationship between social media factors and profitability was discovered. Overall, the study emphasizes the need for business owners/firms/managers to allocate resources toward e-commerce.